Crisis, exposure, imagination : lifting veils - Abong, Fred; Condella, Craig; Miller, Jordan E. (Cambridge Scholars Publishing, 2017)
Unprecedented changes appear to be occurring more often and more rapidly than ever before. We notice these changes and events more readily due to the advent of the information age and the continual technological innovation that has accompanied it. New methods of the manufacture and the dissemination of information expose us to crises in ways previously impossible. These crises often lead to the exposure of new ways of understanding. The lifting of veils allows us to see these crises more clearly. In turn, these epiphanies invite imaginative and creative responses. This volume interprets this s.